Pengaruh Total Utang Dan Total Modal Terhadap Laba Bersih Dengan Pendapatan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Di Jakarta Islamic Index Tahun 2017-2021 - Elvi Yanita; Mellya Embun Baining; Laily Ifazah (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to find out whether total debt and total capital affect net profit with income as a moderating variable for manufacturing companies in the Jakarta Islamic Index for 2017-2021. This study uses data processing research methods in numerical form. The samples in this study are 7 manufacturing companies in the Food and Beverage Sub-Sector on the Indonesian Stock Exchange (IDX) for the 2017-2021 period. The analytical method used is descriptive qualitative and descriptive quantitative. The results of the research on the t-test show that total debt has a significant effect on net income with a value of (0.0008 <0.05), total capital has a significant effect on net income with a value of (0.0000 <0.05). Whereas total debt does not have a significant effect on net income with income as a moderating variable with a value of (0.0638 > 0.05) and total capital does not have a significant effect on net income with income as a moderating variable in manufacturing companies in the Food and Beverage Sub Sector in the Jakarta Islamic Index in 2017-2021 with a value of (0.8553 > 0.05)